Determinants of Islamic bank credit risk in ASEAN countries / Kamarudin Othman ... [et al.] - Othman, Kamarudin; Laidin, Jamilah; Ismail, Shahiszan; Ismail, Nor Azira (Universiti Teknologi MARA, 2020)
Islamic banking system have been establish more than 30 years ago around the world. However, until today it still facing a lot of obstacles especially in term of credit risk. Thus, the aims of this study is to examine the external (macroeconomic) and internal economic factors that influencing Islamic bank credit risk in ASEAN countries. By using 29 of Islamic banking data in ASEAN from years 2011 until 2018, panel data model was applied in this study. The results from the long run regression of FLOMS, DLOS and PMG suggest management efficiency (MGT) and capital ratio (CR) are the internal factors affects the credit risk of ASEAN Islamic bank. Economic growth, inflation and interest rates are external factors that also found could influencing the Islamic bank credit risk. More research ought to be carried out so that one can understand how credit risk is created in Islamic banking. The finding obtained will provide the further understanding of how Islamic banks should tackle the obstacles they face in order to manage their credit risk.